1998
DOI: 10.5914/tropocean.v26i1.2754
|View full text |Cite
|
Sign up to set email alerts
|

Novos registros de espécies de Bathynomus (Crustacea: Isopoda) no Norte do Brasil, coletados durante o Programa Revizee.

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Serejo et al, (2006) B. giganteus is found in the Indian, Pacific and western Atlantic oceans, in the latter case, between Florida and Brazil (Serejo et al, 2006). Similar to the present study, Cintra et al (1998) Loyola e Silva (1999) concluded that B. miyarei occurs throughout Brazilian shelf and slope. The species was collected previously at depths of 312-458 m in the Amapá coast, and 320 m in the Pará coast (Cintra et al, 1998), although it was captured in shallower waters in the Northeast, in Ceará (80 m) and Rio Grande do Norte (22 m).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Serejo et al, (2006) B. giganteus is found in the Indian, Pacific and western Atlantic oceans, in the latter case, between Florida and Brazil (Serejo et al, 2006). Similar to the present study, Cintra et al (1998) Loyola e Silva (1999) concluded that B. miyarei occurs throughout Brazilian shelf and slope. The species was collected previously at depths of 312-458 m in the Amapá coast, and 320 m in the Pará coast (Cintra et al, 1998), although it was captured in shallower waters in the Northeast, in Ceará (80 m) and Rio Grande do Norte (22 m).…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the present study, Cintra et al (1998) Loyola e Silva (1999) concluded that B. miyarei occurs throughout Brazilian shelf and slope. The species was collected previously at depths of 312-458 m in the Amapá coast, and 320 m in the Pará coast (Cintra et al, 1998), although it was captured in shallower waters in the Northeast, in Ceará (80 m) and Rio Grande do Norte (22 m). At the southernmost point of the country (Rio Grande do Sul), the species was collected at a depth of 280 m (Loyola e Silva, 1999).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Currently, its distribution is considered as restricted to the Atlantic Ocean and extends from 31 N, adjacent to the State of Georgia, USA (Lowry & Dempsey, 2006), to 30 S, off the coast of Rio Grande do Sul, Brazil (Soto & Mincarone, 2001). Along the Brazilian coast (Soto & Mincarone, 2001), Bathynomus miyarei has been collected from Amapá (4 N) (Cintra et al, 1998) to Rio Grande do Sul (30 S), between 230 and 800 m deep (Magalhães & Young, 2003).…”
Section: Introductionmentioning
confidence: 99%